1991
DOI: 10.1271/bbb1961.55.829
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation and inhibition of interferon-.BETA. production of human diploid fibroblasts by foodstuffs.

Abstract: We screened for foodstuffs affecting interferon-beta (IFN-beta) production of human foreskin diploid fibroblasts, in the presence of poly I.poly C, cycloheximide, and actinomycin D. alpha- and beta-caseins stimulated IFN-beta production dose-dependently, but kappa-casein inhibited it. Of the two chymosin fragments of kappa-casein, glycomacropeptide was an inhibitor but p-kappa-casein was not. beta-lactoglobulin stimulated IFN-beta production weakly, but lactoferrin inhibited it strongly. It was also shown that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1993
1993
2003
2003

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…In particular, CGP and its carbohydrates have been reported to have various physiological functions: suppression of gastric secretion (Stan et al 1983), growth promoting effect on bifidobacteria (Azuma et al 1984), inhibition of oral actinomyces adhesion to erythrocytes (Neeser et al 1988), inhibition of interferon-/? production by human diploid fibroblasts (Yamada et al 1991), inhibition of cholera toxin binding to ovary cells (Kawasaki et al 1992), and inhibition of influenza virus haemagglutination (Kawasaki et al 1993).…”
mentioning
confidence: 99%
“…In particular, CGP and its carbohydrates have been reported to have various physiological functions: suppression of gastric secretion (Stan et al 1983), growth promoting effect on bifidobacteria (Azuma et al 1984), inhibition of oral actinomyces adhesion to erythrocytes (Neeser et al 1988), inhibition of interferon-/? production by human diploid fibroblasts (Yamada et al 1991), inhibition of cholera toxin binding to ovary cells (Kawasaki et al 1992), and inhibition of influenza virus haemagglutination (Kawasaki et al 1993).…”
mentioning
confidence: 99%
“…Immortalised mammalian cell lines, such as tumour cells, are often used to demonstrate effects of milk proteins on functions related to the immune system. Yamada et al (1991) studied a human fibroblast cell line, and found that several milk-derived proteins (including k-casein, k-caseinderived CGP and lactoferrin) could suppress production of the cytokine interferon-b; in contrast, a-and b-casein enhanced cytokine production, when included in cell culture. Research on bovine lactoferrin by Mattsby-Baltzer et al (1996) has indicated that this protein can suppress lipopolysaccharide-induced secretion of the cytokine IL-6 by a human monocytic cell line (THP-1), when included in in vitro cell culture.…”
Section: Miscellaneous Cell Linesmentioning
confidence: 99%
“…Enhancing activities for IFN-/3 secretion were assessed by adding testing materials in each phase among the three phases. The IFN secreted by the cells into the medium was measured by using a enzyme-linked immunosorbent assay (ELISA) [6,7]. To determine IFN-/3 secreted by cells, 96-well immunoplate was coated with mouse anti-human IFN-/3 monoclonal antibody (Yamasa Shoyu Co., Ltd, Chiba, Japan) overnight at 4 ~ C, reacted with cultured medium of MG63 cells for 20 hr at 4 ~ and then reacted with first antibody (rabbit polyclonal antibody anti-human IFN-/3) (Lee Biomolecular Res Lab, Inc., CA, USA) for 3 hr at 37 ~ The first antibody bound to IFN-/3 was reacted with peroxidase conjugate of goat anti-rabbit IgG antibody for 1 hr at 37 ~ and then reacted with substrate solution containing 0.003% H202, 0.1 M citrate buffer (pH 4.0) and 0.3 mg/ml p-2,2' azino-di-(3-ethylbenzothiazoline-6-sulfonic acid) diammonium salt.…”
Section: Assay Of Enhancement Of Lfn-/3 Secretion By Cellsmentioning
confidence: 99%